Cover Image. Issue 9 (September 2017) - Menys, A.; Keszthelyi, D.; Fitzke, H.; Fikree, A.; Atkinson, D.; Aziz, Q.; Taylor, S. A.
Abstract : The cover image, by A. Menys et al., is based on the Original Article A magnetic resonance imaging study of gastric motor function in patients with dyspepsia associated with Ehlers‐Danlos Syndrome‐Hypermobility Type: A feasibility study, DOI:10.1111/nmo.13090 .